Inteligencia artificial, derecho de autor y obras protegidas: aspectos teóricos y normativos en base al sistema jurídico Ecuatoriano. - Salazar Yánez Alexander Eduardo (2025)
The proposed research aims to study one of the topics that are discussed internationally in different world scenarios. The relationship between copyright and artificial intelligence (AI) is currently of vital importance on a global scale and specifically for Latin America. AI is rapidly transforming the way digital content is created, distributed and consumed. This raises new challenges and questions about intellectual property and copyright. AI-generated works, such as music, art, literature, and software, raise questions about who is the legitimate creator and who has the right to claim ownership over these creations. Also, AI can be used to automate content creation processes, raising ethical and legal questions about originality and creativity. In Latin America, where copyright legislation can vary considerably from country to country, and where access to technology can be unequal, understanding the intersection between copyright and AI is even more important. It is necessary to address these issues from a regional perspective that takes into account the specific realities and needs of the region, promoting a legal framework that encourages innovation and protects the rights of content creators and users. A study is carried out to analyze the theoretical and regulatory foundations on artificial intelligence and Copyright with respect to the rules of protection of works in the Republic of Ecuador based on its expression in international doctrine and Latin American comparative law (Brazil, Chile and Peru). For all this, a legal dogmatic type with a qualitative approach has been proposed in which combined methods of Social Sciences and Legal Sciences are used such as analysis-synthesis, inductive-deductive, comparative law and analytical exegesis. The technique used to develop the research is bibliographic review. 5 As expected results, it is intended to obtain a technical legal study that incorporates the theoretical and regulatory foundations on artificial intelligence and Copyright with respect to the rules of protection of works in the Republic of Ecuador based on its expression in international doctrine and comparative law. Latin American (Brazil, Chile and Peru). Keywords: Copyright, works, artificial intelligence, intellectual property.